Формування та обробка інформації в дифузному середовищі на основі технології обробки великих даних (Big Data) - Шевченко, М. С.; Стрілкова, Т. О. (ХНУРЕ, 2025)
This paper presents a methodology for Big Data processing in the context of modeling the propagation and detection of optical radiation in stochastically inhomogeneous media. A corpuscular-based approach is proposed to account for the random responses of a multi-element photodetector. The use of physical and mathematical models enables the evaluation of the spatiotemporal response, crucial for analyzing diffuse light propagation. The results are based on the physical and technical characteristics of GaAs (gallium arsenide). The proposed approach enhances the analysis of large datasets and facilitates real-time decision making.
Keywords: обробка великих даних; дифузне середовище